2004
DOI: 10.1111/j.1600-6143.2004.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of IL10, TGFβ1, TNFα, and IL4Rα Gene Polymorphisms in Kidney Transplantation: A Collaborative Transplant Study Report

Abstract: Single nucleotide polymorphisms (SNPs) of cytokine genes have been shown to influence cytokine plasma levels. Cytokines are important mediators during organ graft rejection. It was reported that certain cytokine genotypes are associated with improved kidney graft survival. In the present study, SNPs within the IL10 promoter gene, the first exon of the TGFb1 gene, the TNFa promoter gene, and the IL4Ra gene were analyzed in 2298 first and 1901 repeat cadaver kidney recipients. We found no significant effect on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 51 publications
0
32
1
Order By: Relevance
“…It was demonstrated that a TGF-␤ polymorphism in codon 10 was associated with renal function in both adult and pediatric heart transplant recipients (333)(334)(335), although a study in liver transplant recipients could not confirm this association (336). In renal transplantation, TGF-␤ variants in the recipient were not associated with renal allograft outcome in a very large study (337), but this could be explained by the possibility that local TGF-␤ production could depend more on donor genotype than on recipient genotype. Angiotensin converting enzyme (ACE) gene polymorphisms have been associated with serum ACE levels (338).…”
Section: Local Renal Susceptibility Factors For Cni Nephrotoxicitymentioning
confidence: 98%
“…It was demonstrated that a TGF-␤ polymorphism in codon 10 was associated with renal function in both adult and pediatric heart transplant recipients (333)(334)(335), although a study in liver transplant recipients could not confirm this association (336). In renal transplantation, TGF-␤ variants in the recipient were not associated with renal allograft outcome in a very large study (337), but this could be explained by the possibility that local TGF-␤ production could depend more on donor genotype than on recipient genotype. Angiotensin converting enzyme (ACE) gene polymorphisms have been associated with serum ACE levels (338).…”
Section: Local Renal Susceptibility Factors For Cni Nephrotoxicitymentioning
confidence: 98%
“…No associations between the different presumed phenotypes and graft survival were found in first transplant recipients for the loci tested ( [27] in Tables 2 and 3). Repeat transplant recipients with the TNFA rs1800629 (− 308) A/A "high producer" genotype presented lower graft survival.…”
Section: Positive Associations In Kidney Transplant Recipientsmentioning
confidence: 50%
“…Perhaps the largest cohort in a single publication to-date involved 2298 primary transplant recipients and 1901 repeat transplants [27].…”
Section: Positive Associations In Kidney Transplant Recipientsmentioning
confidence: 99%
“…The most interesting -308 variant of the gene has a potential functional effect, being associated with elevated TNF levels (Elahi et al, 2009). One of the first large genetic association studies containing cytokine gene polymorphisms was done by Mytilineos et al (2004). A total of 2,298 first and 1,901 repeat kidney recipients were included in the study involving 73 transplant centres.…”
Section: Cytokine Genes Associate With Poor Outcome Of Kidney Transplmentioning
confidence: 99%
“…A total of 2,298 first and 1,901 repeat kidney recipients were included in the study involving 73 transplant centres. An association was found between the high TNF producer genotype -308A and lower graft survival (P=0.0116 after Bonferroni correction) in retransplant patients (Mytilineos et al, 2004). Other parameters than graft survival were not analysed due to difficulties in getting standardized clinical variables from different centres in the retrospective study.…”
Section: Cytokine Genes Associate With Poor Outcome Of Kidney Transplmentioning
confidence: 99%